Discursive Strategy of the Relationship Between Islam and Democracy on Room for Debate Rubric of nytimes.com - Syahriyani, Alfi; Yuwono, Untung; Wastono, Afdol Tharik (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
Different perspectives on the compatibility between Islam and Democracy are still problematic and have been widely discussed on the international media, especially after the Arab Spring. This study aimed to reveal the changes in social beliefs about the relationship between Islam and democracy within the discourse on Room for Debate rubric, nytimes.com. The data were the written text (verbal) comprising the introductory segment from the editor, the opinion segment comprising 6 articles, and the public comment segment. The method used in this study was the qualitative method. This study employed Faircloughâ€™s Critical Discourse Analysis (CDA) (2013) to reveal the discursive strategy of the writers in negotiating the democratic and Islamic values, to investigate the production, distribution, and consumption of the text, and to identify the social context which causes the discourse of the relationship between Islam and Democracy to appear. The finding showed that there were some democratic values negotiated within the discourse that showed changes in social beliefs about the relationship between Islam and democracy in the modern view. The value negotiation showed the alignment of the writers towards the progressive Muslim actors who supported the modern democratic government system.Â